Desenvolvimento de sistemas líquido cristalinos lamelares contendo diferentes concentrações de Ac-Wahx-kttks para o tratamento do envelhecimento cutâneo - Martinelli, Ariane Migliato [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
During the last decade there has been great interest in lyotropic liquid crystalline systems, being used to the release systems of biologically active agents, the cosmetic, chemical and pharmaceutical industries. One reason for this is that the lyotropic liquid systems exist in many parts of the body such as brain, muscle, retina and many others and their special structure plays an important role in vital movements. Skin aging is a result of intrinsic and/or extrinsic processes. The skin changes resulting from these processes include dyschromia, roughness, fine and persistent wrinkles followed by deeper wrinkles. Among several peptide subfragments of the KTTKS was found to be the minimum sequence necessary to stimulate collagen production by 80% and fibronectin in a variety of mesenchymal cells. Due to the stimulation of collagen synthesis, the KTTKS has attracted great attention as a cosmetic ingredient to provide anti-aging effects. Thinking about all these issues, this master's work aimed to the preparation of lamellar liquid crystalline systems containing different concentrations of Ac-Wahx-KTTKS peptide which has physico-chemical properties that will improve its permeation through the skin. Ac-WAhx-KTTKS peptide was obtained in a purity above 99.97%. The polarized light microscopy and X-ray scattering the low angle allowed to assess that after the incorporation of the peptide did not change phases of the systems, remaining in the lamellar phase. The rheology showed that even after the incorporation of the peptide, the systems continued to show thixotropic (with the exception of formulations F1, F1A and F1B), non-Newtoniano behavior and shear thinning profile. The biosynthesis of collagen in vitro test showed that the peptide is effective in the treatment of skin aging, increasing to 80% in collagen production by fibroblasts. The in vitro tests to the assessment of the release of Ac-Wahx-KTTKS in the formulations showed that the ...

Durante a última década, houve grande interesse em sistemas líquido cristalinos liotrópicos como sistemas de liberação de agentes biologicamente ativos, pela indústria cosmética, química e farmacêutica. Uma das razões é que os sistemas líquido liotrópicos existem em muitas partes do corpo humano, como cérebro, músculo, retina e muitos outros, e a sua estrutura especial desempenha um importante papel nos movimentos vitais. O envelhecimento da pele é o resultado de processos intrínsecos e/ou extrínsecos. As alterações cutâneas resultantes destes processos incluem a discromia, a aspereza, as rugas finas e persistentes seguidas por rugas mais profundas. Entre vários subfragmentos do pró-peptídeo de colágno, o KTTKS foi encontrado para ser a sequência mínima necessária para estimular a produção de colágeno em 80% e de fibronectina em uma variedade de células mesenquimais. Devido à estimulação da síntese de colágeno, o KTTKS tem atraído grande atenção como um ingrediente cosmético para fornecer efeitos anti-envelhecimento. Pensando em todas estas questões, este trabalho de mestrado teve como proposta o preparo de sistemas líquido cristalinos lamelares contendo diferentes concentrações do peptídeo Ac-Wahx-KTTKS, que tem propriedades físico-quimicas que melhorarão sua permeação através da pele. O peptídeo Ac-WAhx-KTTKS foi obtido com um grau de pureza acima de 99,97%. A microscopia de luz polarizada e o espalhamento de raios X a baixo ângulo permitiram avaliar que após a incorporação do peptídeo não houve mudança de fases dos sistemas, permanecendo na fase lamelar. A reologia mostrou que mesmo após a incorporação do peptídeo, os sistemas continuaram a apresentar tixotropia (com exceção das formulações F1, F1A e F1B), comportamento não-Newtoniano e perfil pseudoplástico. O teste de biossíntese de colágeno in vitro mostrou que o peptídeo é eficaz no tratamento do envelhecimento ...
Keywords: Química farmacêutica; Cosmeticos - Industria; Peptídeos; Pele - Envelhecimento; Colageno; Skin Aging